MANAGEMENT OF SPACE IN THE ARCHAEOLOGICAL SITE HUANCHOSMARCA DURING THE LATE INTERMEDIATE - Luján Dávila, Milton (2010)
While the management and use of space at sites in the high altitude basin of Chillón have been studied succinctly, this article proposes to correlate field data conducted in 1998 with several diverse archaeological and ethnohistorical studies for the area. With this perspective we suggest that the site of Huanchosmarca was constructed under a model of asymmetrical growth in a manner directed at the sacred space of Cerro Cahuara or “guardian apu” of this area, a place that was linked to the parcialidad Viscas, the ayllu responsible for the Huanchosmarca and Quecamarca villages.